Determine the Pollution Indices of the Soil Near the Najaf Refinery in the Middle of Iraq - Basha, Noor Th.; Issa, Murtadha J. (Iraqi Journal of Science, 2025)
Al-Najaf refinery produces many pollutants from fuel combustion, such as fumes and gases, which lead to heavy metal pollution in the soil. This research aims to study the pollution factors in the soil surrounding the refinery. Five soil samples were collected from different sites to analyse five heavy metals (Ni, Zn, Co, Cr, and Pb) to determine the chemical pollution level. The results found that the percentage of the metal (Co) in site No.3 was the highest due to its presence near the oil flame and toward the direction of the wind. Three different indices were applied to detect pollution levels: geo accumulation index (I-geo), pollution load index (PLI) and contamination factor (CF). The I-geo for Co, Cr, and Pb showed class 1 relative values, which indicated the sites were only slight pollution, while the I-geo for Zn showed class 2 relative values, which indicated moderate ranges of pollution, and the I-geo for Ni showed class 6 relative values, which indication extremely pollution sites. While the contamination factor for Zn was classed as class 2, indicating moderate contamination, the contamination factors for Co, Cr, Pb, and Ni were all rated as class 1, which indicates low contamination values. PLI levels in all investigated sites categorised as class 1 indicate no pollution (perfection). The gases released by the predominant wind impacted the metal percentage distribution pattern.